PENGARUH PENGGUNAAN BAHASA INDONESIA YANG BAIK DAN BENAR DALAM PERCAKAPAN MAHASISWA PROGRAM STUDI MANAJAMEN INFORMATIKA KOMPUTER ANGKATAN 2015 FAKULTAS EKONOMI UNIVERSITAS MAHAPUTRA MUHAMMAD YAMIN SOLOK TAHUN AJARAN 2015-2016 - Elan Halid (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
Background of this research was student’s communication activity during learning process in classroom that used inapposite Indonesian language based on enhanced spelling (Ejaan Yang Disempurnakan). The using of Indonesian language by Computer Informatics Management program student class of 2015 was still under expectation. It could be seen from conversation that happened in some classes; a lot of them were still doubtful and not confident in using Indonesian language whereas, Indonesian language has been learned since elementary school (SD), junior high school (SMP), senior high school (SMA), and also in college. Aim of this research was to describe the effect of right and good Indonesian language use in student’s conversation in Computer Informatics Management program class of 2015 Economic Faculty University of Mahaputra Muhammad Yamin Solok 2015-2016 school year. This research used qualitative method with descriptive approach by using some techniques: observing technique, listening technique and recording. In analyzing data, the writer listened to the recording of student’s conversation utterance that was uttered by student of Computer Informatics Management program class of 2015. After the data collected, researcher classified and analyzed the result, and it would be displayed descriptively as a form of research presentation. Based on the result and discussion that had been conducted, the conclusions were as well; first they were as many as 41 non standard data, 5 slang words and 1 foreign language that were found from object research, second, lexical meaning was also found as many as 29 data.